A complete denture hygiene maintenance instruction booklet in enhancing elderly behavior: an experimental study - Tsamarah, Bilqis Ghina; Falatehan, Niko; Halim, Stephanie Renata (Universitas Padjadjaran, 2025)
Introduction: The aging process introduces behavioral and physiological challenges, including tooth loss. While complete dentures restore function and aesthetics, inadequate hygiene compromises their effectiveness. Existing educational resources often lack clarity and do not adequately support behavior change. This study aimed to analyze a complete denture hygiene maintenance instruction. Methods: This study employed an experimental one-group pretest and posttest design, involving 37 elderly participants from Panti Jompo Pusaka 41 Yayasan Al-Madiniyah. A 15-item questionnaire was administered through structured interviews both before and two weeks after the distribution of a booklet on denture hygiene maintenance instruction techniques. The Wilcoxon signed-rank test was used to analyze differences. Results: Following the two-week intervention, 78% of participants achieved good knowledge scores, 84% demonstrated good attitudes, and 73% reported good hygiene practices. Wilcoxon analysis showed significant improvements across all three domains (p=0,001). Conclusion: The use of instructional booklets can enhance a complete denture hygiene maintenance instruction among the elderly. Although behavior is presented as an overall outcome, the analysis was conducted independently for each domain to ensure interpretive clarity.